Policy Towards the ‘Auditorium Culture Sector’ in Poland in the First Year of the COVID-19 Pandemic: Mechanisms of Restrictions and Support with Public Funds, Including State Aid - Obłąkowska, Katarzyna; Bartoszewicz, Artur (Journal of Public Governance, 2022)
Objectives: The objective of the article is to describe the public policy in the first year of the COVID-19 pandemic towards the auditorium culture sector in the Republic of Poland. This policy was stretched between the anti-pandemic policy and the anti-crisis policy, and it appeared in the end as the policy for the hibernation of the auditorium culture sector. Research Design & Methods:The methods used to prepare the article involved juridical exegesis, desk research, as well as legal, sociological, and economic analyses. Findings:Public authorities in Poland wanted the institutions, enterprises, and creators in the auditorium culture sector to survive the period of the pandemic. Implications / Recommendations: The article denotes what the auditorium culture sector is according to the authors. It shows the importance of operation of theatres, cinemas, museums, art galleries, historical places, cultural centres, libraries, archives, and creators for the Polish society and economy. It presents the tools of policy against the COVID-19 pandemic and seven phases of the anti-pandemic policy, with the consequences for the auditorium culture sector. It describes the scale of the disturbance in the activity of the auditorium culture sector, and mechanisms of anti-crisis and hibernating intervention towards this sector. The support intervention for the sector is described in detail; the article presents programmes and numbers. The aid for the institutions and creators in the auditorium culture sector in Poland during the first year of the COVID-19 pandemic was provided by the central government, local governments, non-governmental organisations (sectoral NGOs), public cultural institutions, and artistic schools. Contribution / Value Added:The article based on the “lesson learnt” method brings knowledge to public policy and for decision-makers in the face of future threats of a similar type.